FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI DASAR PADA BALITA DI WILAYAH KERJA PUSKESMAS KOLOK KOTA SAWAHLUNTO - KURNIATI MAYA SARI WD (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Immunization comes from the words immune, immune and resistant. Children are immunized, meaning they are given immunity against certain diseases. Children are immune or resistant to one disease but not necessarily immune to other diseases. So, immunization is an effort to actively generate / increase a person's immunity against a disease, so that if one day they are exposed to the disease, they will not get sick or only experience mild illness. The achievement of basic immunization in the working area of PuskesmasKolok is currently still low (67.3%) compared to other Puskesmas in Sawahlunto City. This study aims to determine the factors related to the completeness of basic immunization for children under five in the Work Area of PuskesmasKolok Kota Sawahlunto in 2017. This type of research is descriptive analytic. This research was conducted in the working area of PuskesmasKolok, Sawahlunto City on 11 to 15 December 2017. The population in this study were all mothers who had toddlers aged 12-23 months. A total of 61 respondents. Data were collected through interviews using a questionnaire. Then the data is processed using computerization, then analyzed by univariate and bivariate after that it is interpreted. The results of the study more than half (76%) of respondents have poor knowledge, more than half (72.2%) of respondents have a job, more than some (84.4%) of respondents have no family support, there is a significant relationship between maternal knowledge With the completeness of basic immunization for children under five, there is a significant relationship between the work status of the mother and the completeness of basic immunization for children under five, and there is a significant relationship between family support and completeness of basic immunization for children under five in the Work Area of PuskesmasKolok Kota Sawahlunto in 2017. It is hoped that the officers will increase regular outreach on every community activity such as posyandu about the impact of not immunizing babies. In the working area of Puskesmas Kolok, Sawahlunto City. Keywords: Immune, Children, Puskesmas Kolok, Sawahlunto City.